Advanced interatrial block and ischemic stroke: The Atherosclerosis Risk in Communities Study. (26th July 2016) - O'Neal, Wesley T.; Kamel, Hooman; Zhang, Zhu-Ming; Chen, Lin Y.; Alonso, Alvaro; Soliman, Elsayed Z.
Abstract : Objective: Given that recent reports have suggested left atrial disease to be an independent risk factor for ischemic stroke, we sought to examine if advanced interatrial block (aIAB) is an independent stroke risk factor. Methods: We examined the association between aIAB and incident ischemic stroke in 14, 716 participants (mean age 54 ± 5.8 years; 55% female; 26% black) from the Atherosclerosis Risk in Communities Study (ARIC). Cases of aIAB were identified from digital ECGs recorded during the baseline ARIC visit (1987–1989) and the first 3 follow-up study visits (1990–1992, 1993–1995, and 1996–1998). Adjudicated ischemic stroke events were ascertained through December 31, 2010. Results: There were 266 (1.8%) participants who had evidence of aIAB. Over a median follow-up of 22 years, 916 (6.2%) ischemic stroke events were detected. The incidence rate (per 1, 000 person-years) of ischemic stroke among those with aIAB (incidence rate 8.05, 95% confidence interval [CI] 5.7, 11.4) was more than twice the rate in those without aIAB (incidence rate 3.14, 95% CI 2.94, 3.35). In a multivariable Cox regression analysis adjusted for stroke risk factors and potential confounders, aIAB was associated with an increased risk of ischemic stroke (hazard ratio 1.63, 95% CI 1.13, 2.34). The results were consistent across subgroups of participants stratified by age, sex, and race. Conclusions: In the ARIC, aIAB was associated with incident ischemic stroke, which strengthens the hypothesis that left atrial disease should be considered an independent stroke risk factor.